Modulation in phase and frequency of neural oscillations during epileptiform activity induced by neonatal Zika virus infection in mice - Pinheiro, Daniel J. L. L.; Oliveira, Leandro F.; Souza, Isis N. O.; Brogin, Joao A. Ferres [UNESP]; Bueno, Douglas D. [UNESP]; Miranda, Iranaia Assuncao; Da Poian, Andrea T.; Ferreira, Sergio T.; Figueiredo, Claudia P.; Clarke, Julia R.; Cavalheiro, Esper A.; Faber, Jean (Nature Publishing Group, 2020)
Modulation of brain activity is one of the main mechanisms capable of demonstrating the synchronization dynamics of neural oscillations. In epilepsy, modulation is a key concept since seizures essentially result from neural hypersynchronization and hyperexcitability. In this study, we have introduced a time-dependent index based on the Kullback-Leibler divergence to quantify the effects of phase and frequency modulations of neural oscillations in neonatal mice exhibiting epileptiform activity induced by Zika virus (ZIKV) infection. Through this index, we demonstrate that fast oscillations (gamma and beta 2) are the more susceptible modulated rhythms in terms of phase, during seizures, whereas slow waves (delta and theta) mainly undergo changes in frequency. The index also allowed detection of specific patterns associated with the interdependent modulation of phase and frequency in neural activity. Furthermore, by comparing ZIKV modulations with the general computational model Epileptors, we verify different signatures related to the brain rhythms modulation in phase and frequency. These findings instigate new studies on the effects of ZIKV infection on neuronal networks from electrophysiological activities, and how different mechanisms can trigger epilepsy.